Strategi Meningkatkan Minat Beli Konsumen Melalui Social Marketing, Endorserment Selebgram dan Potongan Harga - Orfyanny S. Themba; Buyung Romadhoni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to examine the effect of social marketing on consumer buying interest, to test the effect of celebrity endorsements on consumer buying interest, to test the effect of price discounts on consumer buying interest. The population of this study were 465 students from the faculty of economics and business majoring in management class of 2019 at the Muhammadiyah University of Makassar. The sampling technique in this study is classified as non probability sampling with purposive sampling or sampling based on certain characteristics. In this study the authors used a closed questionnaire, namely statements and questions with a certain number of answers as choices. So that the total sample is 90 respondents. The data analysis technique used in this research is quantitative analysis with multiple linear regression analysis method. Based on the results of statistical tests that have been carried out, this study found that social marketing, Selebgram Endorsements and price discounts have a positive and significant effect on consumer buying interest.